Early detection of macular changes in patients with diabetes using Rarebit Fovea Test and optical coherence tomography. Issue 12 (25th June 2007) - Nilsson, M; von Wendt, G; Wanger, P; Martin, L
Abstract : Aim: To evaluate central retinal thickness and foveal function using optical coherence tomography (OCT) and the Rarebit Fovea Test (RFT) in patients with diabetes without previously known retinopathy or maculopathy. Method: Forty-two patients with diabetes mellitus (DM) were selected from the screening records at St Erik Eye Hospital. Inclusion criteria were absence of macular or other retinal changes at previous screening examination and best corrected visual acuity ⩾1.0. These patients and 42 healthy controls were examined with the recently developed RFT, and retinal thickness was measured using OCT. Lens thickness and light scatter were evaluated by Scheimpflug photography. Results: Significantly more DM subjects (12/42) had a subnormal RFT result compared with the controls (2/42) (p = 0.007). None of the 12 DM subjects had maculopathy, one had mild non proliferative diabetic retinopathy, and five had minimal non-proliferative diabetic retinopathy. The retinal thickness in the pericentral zone was significantly (p<0.05) thinner in DM patients with subnormal RFT compared with the controls. Conclusion: Decreased RT and subnormal RFT results were found in a subgroup of diabetes patients, despite normal screening results. Prospective studies are under way to evaluate the prognostic implications.